Towards the Development of a Digital Marketing (DM) Competencies Framework - Papageorgiou, George; Mihai, Simona; Ioannou, Myria; Marouchou, Despina; Marneros, Stelios (My University, 2020)
Developing an effective marketing program presents a great challenge for many firms in today's digital economy. It seems there is a lack of key competencies as many organizations fail to incorporate current developments of today's digitally interconnected world in their communications strategy. As all forms of conducting business become digital, especially marketing communications and the process of introducing new products in the market need a new approach which capitalizes on the recent technological advancements. This paper, proposes a Digital Marketing (DM) competency profile that every effective marketer should possess. The proposed DM framework incorporates latest developments in technology combined with the essential needs of the industry. The development of the DM framework is based on an extensive literature review on DM studies and empirical evidence from marketing managers. The framework could be of great value to businesses, which could thereby effectively evaluate their competency levels and take action to improve their performance.
Keywords: Information and Communication Technology (ICT); Digital Marketing; Digital Communications; Education; Marketing communications; Communications Strategy